Building strong communities through mediation in Malaysia: The need for a legal framework - Abdul Hak, Nora; Ambaras Khan, Hanna (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
The Malaysian government, through the Department of National Unity and Integration (DNUI) has decided in 2007 to introduce community mediation as a means of resolving community disputes, as this is well established in countries like Singapore, Australia, the UK, United States, amongst others. In Malaysia, there is no legal framework as yet developed for community mediation. Thus, the aim of this paper to explore the need for establishing such a framework, which for example, in Singapore, clearly establishes and promotes community mediation practice in the population. The writings in the history and establishment of community mediation and of the framework in countries that have this legal entity are looked into. Besides library research, the study organized interviews and discussions with firstly, the relevant authorities and policy makers with respect to current status, planning and development of community mediation. Secondly, descriptions and opinions of the practitioners of mediation such as community leaders, rukun tetangga activists, members of resident associations and possibly with individuals with the knowledge and experience in these disputes. The total sums of descriptions, experiences and opinions helps discern the need of a legal framework for community mediation. It helps improve and promote the practice of community mediation in managing to resolve community disputes and conflicts